2001
DOI: 10.1002/ajpa.1109
|View full text |Cite
|
Sign up to set email alerts
|

Variation in body mass index among Polish adults: Effects of sex, age, birth cohort, and social class

Abstract: Variation in the body mass index (BMI) among occupationally active inhabitants of one Polish urban center was studied by means of a three-factor ANOVA. The material is cross-sectional and comprises 32,750 men and women aged 22-60 years, examined in five successive surveys between 1983-1999. The factors considered in each sex were: 1) age category, 2) year of examination, and 3) social class. The increase of BMI with age is markedly greater among women than among men. No sustained intergeneration trend towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The data were from an ongoing study of the prevalence of obesity in the urban population of Wroclaw, located in southwestern Poland. Initial analyses indicated significant interactions and influences of age and socioeconomic status on the BMI in adult men and women (Bielicki et al, 2001). This study extends the analysis to age-associated changes in the BMI in three homogeneous socio-occupational groups among men and women.…”
Section: Methodssupporting
confidence: 51%
“…The data were from an ongoing study of the prevalence of obesity in the urban population of Wroclaw, located in southwestern Poland. Initial analyses indicated significant interactions and influences of age and socioeconomic status on the BMI in adult men and women (Bielicki et al, 2001). This study extends the analysis to age-associated changes in the BMI in three homogeneous socio-occupational groups among men and women.…”
Section: Methodssupporting
confidence: 51%
“…In contrast, in a study in Bremerhaven, Germany, no significant trend was observed among 6‐year‐old children over the period of 1968 to 1987 using health records of the City Health Centre (Danker‐Hopfe & Roczen 2000). Also in another study in Poland no BMI trend was observed in a Polish study in an urban centre during 1983 to 1999 on 32 750 male and female individuals (Bielicki et al . 2001).…”
Section: Discussionmentioning
confidence: 95%
“…These observations are usually based on crosssectional studies (1)(2)(3)(4)(5) . However, such age-BMI relationships may result from mixed effects of ageing per se, characteristics of subsequent birth cohorts and selective survival.…”
Section: Adults Ageing Body Weight Cohort Longitudinalmentioning
confidence: 99%